Berebut Makna Lewat Dui’ Menre’: Analisis Mengenai Ideologi dalam Perkawinan Bugis - Arham Rahman (Sanata Dharma University, 2020)
The rite of dui’ menre’ bestowal in Bugis marriage positions women as object of exchange. However, this rite generates contradictory effect. On one hand, it is perceived as burdensome because the broom parties have to give a relatively big amount of money to the bride parties. On the other hand, the Bugenese keep running the rite. Hence, the rite of dui’ menre’ is not only a ritual of giving-and-taking money, but also an ideological conduct. There is something powerful that forces people to keep doing the rite solemnly. This research lead me to conduct this research. There are two objectives of the reserach. First, it tries to find the form of ideology and fantasy which support the rite of dui’ menre’ be towal; second, it wants to expose the Bugenese sub ject position in the face of dui’ menre’ bestowal. The fieldwork was conducted in Pinrang district, South Celebes.To discuss the matter, this research utilizes Ideological Criticism and Sexuation developed by Slavoj Zizek from Lacanian concepts. Slavoj Zizek’s Ideological Crit icism is used to find out the fantasy which supports an ideology. Meanwhile, sexuation is utilized to show the impossibility of sexual relation defined by Bugenese through dui’ menre’ r ite.Dui’ menre’ is not only a language of tradition as it were in the era of traditional authority, but also a languageof economy which makes woman as an object of exchange. Dui’ menre ‘ is a challenge that must be conquered by a man to get a woman. In the contemporary era, several forces collide. Bugis feudalism, Islam, and capitalism interweave in the same issue. In the rite of ui’ menre’, woman is reduced to be object cause of desire for man. In this symbolic realm the Bugenese subjects present and take position. Generally, there are several Bugis subject positions in responding dui’ menre’, na mely psychosis, perve rse, obsess ive neurotic, and histeria.